Protein Energy Malnutrition Impairs Homeostatic Proliferation of Memory CD8 T cells - Iyer, Smita S. (2011)
Nutrition is a critical but poorly understood determinant of immunity. There is abundant epidemiological evidence linking protein malnutrition to impaired vaccine efficacy and increased susceptibility to infections; yet, the role of dietary protein in immune memory homeostasis remains poorly understood. Here we show that protein energy malnutrition (PEM) induced in mice by low-protein (LP) feeding has a detrimental impact on CD8 memory. Relative to adequate-protein (AP) fed controls, LP feeding in lymphocytic choriomeningitis virus (LCMV) immune mice resulted in a 2-fold decrease in LCMV-specific CD8 memory T cells. Adoptive transfer of memory cells, labeled with a division tracking dye, from AP mice into naive LP or AP mice demonstrated that PEM caused profound defects in homeostatic proliferation. Remarkably, this defect occurred despite the lymphopenic environment in LP hosts. While antigen-specific memory cells in LP and AP hosts were phenotypically similar, memory cells in LP hosts were markedly less-responsive to poly(I:C)-induced acute proliferative signals. Furthermore, upon recall, memory cells in LP hosts displayed reduced proliferation and protection from challenge with LCMV-clone 13 resulting in impaired viral clearance in the liver. The findings show a metabolic requirement of dietary protein in sustaining functional CD8 memory and suggest that interventions to optimize dietary protein intake may improve vaccine efficacy in malnourished individuals.